PENGARUH KUALITAS PRODUK DAN PENETAPAN HARGA TERHADAP KEPUTUSAN PEMBELIAN (Studi Produk Sampingan PT Perkebunan Nusantara V Pekanbaru) - Noorasha Raquel Ridho; Meyzi Herianto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to determine the effect of product quality and pricing on the purchase decision by-products at PT Perkebunan Nusantara V Pekanbaru. The method used in this research is descriptive and quantitative statistics with explanatory research. The sample in this study amounted to 50 respondent who were determined using the census technique and using a questionnaire for data collection techniques. From the data analysis which includes validity test, reliability test, linear regression analysis, hypothesis testing and coefficient of determination test, the results show that product quality has a significant effect on purchasing decisions by t count (9.089) > t table (1,676), pricing has a significant effect on decision purchase of t count (5.521) > t table (2.009) and the results of the F test of product quality and pricing on purchasing decisions show a value of 74.5%, meaning that product quality and pricing simultaneously have a significant effect on purchasing decisions at PT Perkebunan Nusantara V Pekanbaru. Keywords : Product Quality, Pricing and Purchase Decision.